Age Polyethism in Atta sexdens (Linnaeus) (Hymenoptera: Formicidae) - Fabrícia Gonçalves Lacerda; Leandro Sousa-Souto; Terezinha Maria Castro Della Lucia; Danival José de Souza (Sociobiology, 2020)
This study aimed to verify age polyethism occurrence in medium-sized (cephalic capsule = 2.3 ± 0.21 mm) and small-sized (cc = 1.4 ± 0.10 mm) workers from Atta sexdens (Linnaeus) colonies. Four laboratory colonies were used, and they were maintained at 25 ± 2 °C, with 75 ± 3% relative humidity and a 12-hour photoperiod. Workers from these colonies were marked after their emergence and observed throughout their lifetime to determine which tasks they performed. The number of ants performing each activity was analyzed using linear mixed-effect models (LME), considering the temporal effect and the block design (colonies). We found that fungal garden maintenance tasks were frequent for both sizes, but their occurrence decreased significantly from the ninth week. The foraging activity occurred gradually in both sizes, with stabilization in the number of workers from the fourth week onwards and declined in the last three weeks of lifespan. Waste management tasks occurred throughout life but were more frequent during the first two weeks of life, in both medium and small workers. Therefore, age polyethism may be related to all activities; however, foraging tasks presented a distinct pattern compared to tasks in the fungus garden and refuse dump, where younger ants were more frequently observed.